CLINICAL AND MORPHOLOGICAL ASPECTS OF MULTIPLE PRIMARY MALIGNANT SKIN TUMORS. - Solmetova M.N; Gafur-Akhunov M.A; Vaisov A.Sh; Yuldasheva D.Yu (Scholar Express Journals, 2021)
Malignant diseases, predominantly affecting the aging generation over 60 years of age, are distinguished by their particular insidiousness, manifesting their likelihood of multiple lesions of the same individual by tumors of a different nature. Such cases, called primary multiple malignant tumors (PMMT), have become not rare, and manifest themselves in all the variety of oncological pathology. The authors conducted a unique study of PMMT on a large material - cancer patients - residents of Tashkent, having comprehensively studied the situation with PMMT for a separate period of time (2018-2019), identified and studied all cases of combination with skin cancer. Further, focusing on the most common form of cancer in the elderly population in general - basal cell skin cancer, we drew parallels of the frequency of occurrence of PMMT with a separate histotype. A high percentage of PMMT occurrence in basal cell carcinoma was established - more than 60%, especially in micronodular histotype. These data require careful clinical examination of patients with basal cell carcinoma of the skin for not only relapse of the disease, but also for early detection of a second independent cancer of any localization, both skin and any other organ. The article will be useful not only for specialists associated with skin pathologies - oncologists and dermatologists, but also for general practitioners who conduct dispensary control of the attached population registered on oncology, especially among the elderly.
Keywords: Basal cell skin cancer; multiple primary malignant tumors; pathologies